Incorporating funding costs in top-down stress tests - Korsgaard, Søren (Journal of Financial Stability, 2021)
Central banks and supervisory authorities regularly conduct stress tests of banks. As losses accumulate in stress scenarios, banks’ equity position worsens, and they must pay higher interest rates to retain funding. I explore how variations of Merton-type models can be used to measure bank risk, and then examine the link between various risk measures and funding costs. Finally, I outline a method for incorporating funding cost increases into top-down stress tests.